Asymmetric, Three‐Component, One‐Pot Synthesis of Spiropyrazolones and 2, 5‐Chromenediones from Aldol Condensation/NHC‐Catalyzed Annulation Reactions. Issue 15 (18th February 2016) - Wang, Lei; Li, Sun; Chauhan, Pankaj; Hack, Daniel; Philipps, Arne R.; Puttreddy, Rakesh; Rissanen, Kari; Raabe, Gerhard; Enders, Dieter
Abstract: A novel one‐pot, three‐component diastereo‐ and enantioselective synthesis of spiropyrazolones has been developed involving the aldol condensation of an enal to generate α, β‐unsaturated pyrazolones, which react with a second equivalent of enal through an N‐heterocyclic carbene (NHC)‐catalyzed [3+2] annulation. The desired spirocyclopentane pyrazolones are obtained in moderate to good yields and good to excellent stereoselectivities. Alternatively, starting from cyclic 1, 3‐diketones, 2, 5‐chromenediones are available through [2+4] annulation. Abstract : Aldol/NHC cooperation : Three‐component, one‐pot, aldol condensation/N‐heterocyclic carbene (NHC)‐catalyzed [3+2] annulation reations have been developed to steroselectively assemble spiropyrazolones through an azolium homoenolate pathway. By simply replacing the pyrazolones by diketones, highly substituted 2, 5‐chromenediones are obtained through a [2+4] annulation reaction by an azolium enolate route.